Tuottavuuskehityksen eriytyminen: Karkaavatko eturintaman yritykset muilta?; Productivity Divergence – Frontier Firms vs. the Others - Mika Pajarinen; Petri Rouvinen; Ilkka Ylhäinen (The Research Institute of the Finnish Economy (ETLA), 2017)
– International literature suggests that productivity growth of the global frontier firms – those in the best five percent – has diverged from the others during the 2000s. We study this issue using Finnish firm-level data. We find that the productivity of the Finnish frontier firms does not diverge from the others to such a degree as in the international comparisons. The findings do not provide clear evidence of a slowdown in the diffusion process. We also analyze whether frontier firms are associated with characteristics related to digitalization – and do not find clear evidence of that either. This might be related to the fact that the employed measures are related to technology adoption – not to the creativity or efficiency of its use.
Keywords: D22; O30; O40; 330; Productivity; Divergence; Diffusion; Ddigitalization; Finland; Produktivität; Betriebsgröße; Unternehmen; Computerunterstützung; Automatisierung; Finnland